Denotative and Connotative Meaning in Bugis: Undergraduate Semantic Competence in a Multilingual Teacher Education Context - Andi Fatimah Junus (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study investigates how undergraduate students conceptualise and articulate denotative and connotative meanings in Bugis, a major regional language in South Sulawesi, Indonesia. Framed within semantic theory, cognitive linguistics, and Cultural Linguistics, the research responds to a gap in the literature that has largely focused on Bahasa Indonesia while overlooking regional languages as sites of semantic and cultural competence. Using a qualitative descriptive design supported by descriptive statistics, data were collected from written assignments completed by 11 first-year students in a language and literature education programme. Each student produced one denotative and one connotative Bugis sentence and provided written explanations of meaning. Responses were scored separately for denotative and connotative accuracy and analysed through thematic coding. Findings show that students exhibit near-perfect mastery of denotative meaning (M = 48.6/50), with highly consistent performance across participants. By contrast, connotative meaning (M = 46.8/50) reveals greater variability in depth, clarity, and cultural precision. Qualitative analysis identifies four interpretive patterns: reliance on familiar metaphors, emotional and relational focus, limited metalinguistic vocabulary, and strong influence of cultural familiarity. These results suggest that while literal semantic competence is well established, figurative competence remains uneven and deeply tied to cultural experience. The study argues that semantics teaching in teacher education should explicitly incorporate regional languages such as Bugis as rich semantic and cultural resources, foregrounding figurative language, metalanguage, and multilingual repertoires to strengthen future teachers’ ability to guide learners across literal and figurative levels of meaning.